Effort of Chhattisgarh to design new B.Ed. syllabus in the context of NCTE Regulation 2014 - Chakraborty, Utpal (Voices of Teachers and Teacher Educators, 2015)
Chhattisgarh state has, in the recent past, revised and implemented the D.Ed. programme. Our initial attempt to design School Experience Programme for two year D.Ed. course in 2005 was met with some reservations on the part of DIETs and BTIs as D.Ed. curriculum is the subject of Board of Secondary Education (the new programme was designed by the SCERT, Raipur). However, in 2007, SCERT again started work on D.Ed curriculum in conformity with NCF 2005 with the help of NCERT, RIE (Bhopal), Digantar, Vidya Bhawan, Ekalavya, IFIG and Azim Premji Foundation. The principals and PST members of all DIETs and BTIs participated in this exercise. Through a series of workshops, a course outline was developed and guidelines of school experience programme were prepared and tried out in DIETs and BTIs.